1994
DOI: 10.1182/blood.v84.8.2815.2815
|View full text |Cite
|
Sign up to set email alerts
|

In vivo T-cell clonal amplification at time of acute graft-versus-host disease

Abstract: In a series of patients transplanted with HLA-matched allogeneic bone marrow grafts (alloBMT), we previously showed that a few T-cell receptor (TCR) V alpha and V beta gene segment transcripts were overexpressed in skin compared with blood at the time of acute graft- versus-host disease (aGVHD). Here, in one selected patient with overexpressed V beta 16 and V alpha 11 transcripts in skin, we analyzed the junctional variability of these transcripts in donor blood, patient blood, and skin collected at aGVHD onse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Persisting clonal expansions are not necessarily an expression of a malignant process; they also represent clonal or oligoclonal expansion of possibly autoreactive T cells and are most marked in CD8+ populations. The increase of CD57 expression by the CD8+ cells, as well as the demonstration of expanded TCR VB families expressing CD57, are characteristic features of diseases attributable to an activated immune environment such as acute graft vs. host disease, multiple sclerosis and rheumatoid arthritis [61–63]. In these well‐established autoimmune disorders clonally expanded T cells bearing similar VB subfamilies proliferate dominantly in different patients, reflecting a specific response of auto‐reactive T cells to certain antigens.…”
Section: Immune Pathophysiology Of Myelodysplastic Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…Persisting clonal expansions are not necessarily an expression of a malignant process; they also represent clonal or oligoclonal expansion of possibly autoreactive T cells and are most marked in CD8+ populations. The increase of CD57 expression by the CD8+ cells, as well as the demonstration of expanded TCR VB families expressing CD57, are characteristic features of diseases attributable to an activated immune environment such as acute graft vs. host disease, multiple sclerosis and rheumatoid arthritis [61–63]. In these well‐established autoimmune disorders clonally expanded T cells bearing similar VB subfamilies proliferate dominantly in different patients, reflecting a specific response of auto‐reactive T cells to certain antigens.…”
Section: Immune Pathophysiology Of Myelodysplastic Syndromesmentioning
confidence: 99%
“…Hypothetical models propose immune triggering of the effectors’ lymphocytes, either by aberrantly expressed oncogenes and fusion genes in the haematopoietic progenitor cells or by super‐antigens derived from bacteria or viruses [52,64]. Such effector cells should have limited TCR usage among different MDS patients, reflecting the common pathogenic, antigen‐driven oligoclonal expansion [61–63].…”
Section: Immune Pathophysiology Of Myelodysplastic Syndromesmentioning
confidence: 99%
“…Analysis of the TCR has been employed in the study of classical autoimmune diseases [9][10][11][12][13][14][15][16][17], and T-cell lymphoproliferative disorders [18][19][20][21]. During the acute stage of infectious or autoimmune diseases, antigen-drive expansion will lead to over-representation of immunodominant T-cell clones reflected in VB and CDR3 skewing.…”
Section: Molecular Basis Of the T-cell Receptor Diversity And Experimmentioning
confidence: 99%
“…Skewing of the T-cell VB spectrum has also been described for many animal models of autoimmune diseases, such as encephalitis [10,23] and thyroiditis [11]. In humans, expansion of specific CDR3 VB TCR clones has been found in multiple sclerosis [12], type I diabetes mellitus [13], rheumatoid arthritis [14,15,24], primary biliary cirrhosis [16], psoriasis [17,25], and during graft-versus-host disease (GvHD) [4,9,[26][27][28][29]. Powerful pathologic effects of the immune system observed in autoimmune diseases, such as aplastic anemia (AA) demonstrate the potential for immunebased cellular therapies and vaccinations in the treatment of malignant disorders, including leukemia.…”
Section: Molecular Basis Of the T-cell Receptor Diversity And Experimmentioning
confidence: 99%
“…On the other hand, while bone marrow harvests require no mobilization therapies and can often be done in a single one-day collection, the pain associated with bone marrow harvests may take 2 to 4 weeks to subside 17,18 . In addition, various studies have reported a decreased time for reconstitution of the immune system, less transplant-related toxicities and mortalities, and a decreased rate of GVHD occurrence in peripheral blood stem cell recipients compared to bone marrow recipients [19][20][21][22][23] .…”
Section: Types Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%